Application of STEM-based LKPD on Reaction Rate Material to Improve Students' Critical Thinking Ability - Aulia Rahmah; Gulmah Sugiharti (Universitas Negeri Medan, 2023)
The use of STEM-based LKPD can improve students' critical thinking skills. In this study, non-test instruments such as validation questionnaires and test instruments with 5 aspects of critical thinking were used. This study aims to 1) measure the validity of the developed LKPD; 2) determine students' responses to the developed LKPD; 3) determine the improvement of students' critical thinking skills; 4) determine whether students' critical thinking skills on the use of STEM-based LKPD developed better than without using STEM-based LKPD. Data collection techniques through BSNP questionnaire, student response questionnaire and N-Gain test for critical thinking improvement and right-sided t test. The samples were 70 students of class XI F1B and XI F2D who were randomly selected. Based on the material and media expert validators, it shows that 94.34% of the material experts and 87.5% of the developed LKPD media experts have a very high interpretation and the level of validity is